RECEPTION OF ROLE MAS-MEDIA IN THE LIFE OF SOCIETY IN SOCIO-PHILOSOPHICAL AND CULTURALOGICAL THEORIES OF XX ST. - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article deals with the socio-philosophical and culturological theories of the XXth century, devoted to the reception of media culture in the life of society. The comprehensive study of the influence of media culture on the social and cultural spheres of historical being reveals the system-forming functions of this phenomenon, its transformative impact on man, social groups and institutes of society. The research substantiates that, by denying the communicative forms of the previous cultural-historical epoch, the new media removes their elements, synthesizing more complex mechanisms of information and communication activity and strengthening the complex influence on man and society, forming new systems of social relations, mediating the socio-cultural sphere of society with communication technologies.